PPARα-mediated peroxisome induction compensates PPARγ-deficiency in bronchiolar club cells - Karnati, Srikanth; Oruqaj, Gani; Janga, Harshavardhan; Tumpara, Srinu; Colasante, Claudia; Van Veldhoven, Paul P.; Braverman, Nancy; Pilatz, Adrian; Mariani, Thomas J.; Baumgart-Vogt, Eveline (PLOS ONE, 2018)
Despite the important functions of PPARγ in various cell types of the lung, PPARγ-deficiency in club cells induces only mild emphysema. Peroxisomes are distributed in a similar way as PPARγ in the lung and are mainly enriched in club and AECII cells. To date, the effects of PPARγ-deficiency on the overall peroxisomal compartment and its metabolic alterations in pulmonary club cells are unknown. Therefore, we characterized wild-type and club cell-specific PPARγ knockout-mice lungs and used C22 cells to investigate the peroxisomal compartment and its metabolic roles in the distal airway epithelium by means of 1) double-immunofluorescence labelling for peroxisomal proteins, 2) laser-assisted microdissection of the bronchiolar epithelium and subsequent qRT-PCR, 3) siRNA-transfection of PPARγand PPRE dual-luciferase reporter activity in C22 cells, 4) PPARg inhibition by GW9662, 5) GC-MS based lipid analysis. Our results reveal elevated levels of fatty acids, increased expression of PPARα and PPRE activity, a strong overall upregulation of the peroxisomal compartment and its associated gene expression (biogenesis, α-oxidation, β-oxidation, and plasmalogens) in PPARγ-deficient club cells. Interestingly, catalase was significantly increased and mistargeted into the cytoplasm, suggestive for oxidative stress by the PPARγ-deficiency in club cells. Taken together, PPARα-mediated metabolic induction and proliferation of peroxisomes via a PPRE-dependent mechanism could compensate PPARγ-deficiency in club cells.